1662 Closure of Oro-Antral Fistulae in Conjunction with Functional Endoscopic Sinus Surgery: A Retrospective Analysis + Systematic Review. (12th October 2021) - Aruede, G; Smart, K; Mustafa, S
Abstract: Aim: The aim of this study was to evaluate the surgical closure of OAFs created following dental extractions in conjunction with FESS in adult patients within a hospital in South Wales, UK, during a 5-year period, from 1 st January 2014 to 31 st December 2018, with a systematic review of the literature to investigate success rates. Method: A manual search in the hospital's theatre system for surgery between 2014 and 2018 containing codes for FESS, OAC or OAF was completed. These were screened for joint cases, and the patient's hospital numbers entered into a Microsoft Excel spreadsheet. A retrospective analysis of their clinical records was performed. Success was measured as total closure and relief of sinusitis after 1 month. The PRISMA format was used to complete the systematic review. Results: 13 patients (mean age 51 ± 12.44, 7:6 male to female) met the inclusion criteria. The most common cause was extraction of the maxillary first molar. A 100% success rate was achieved, with no patients requiring revision surgery. The systematic review highlighted an average success rate of 98.7%. A protocol for the management of OACs was designed in both English and Welsh and distributed to Primary Care Dentists within South Wales. Conclusions: OAF closure with FESS can be considered as a highly effective approach, leaving patients symptom free. It is important that protocols are in place for dentists suspecting an OAC in order to expedite patient management.